2002
DOI: 10.1038/sj.leu.2402573
|View full text |Cite
|
Sign up to set email alerts
|

Schedule-dependent synergism and antagonism between methotrexate and cytarabine against human leukemia cell lines in vitro

Abstract: Methotrexate (MTX) and cytarabine have been widely used for the treatment of acute leukemias and lymphomas for over 30 years. However, the optimal schedule of this combination is yet to be determined and a variety of schedules of the combination has been used. We studied the cytotoxic effects of MTX and cytarabine in combination against human leukemia cell lines at various schedules in vitro. The effects of the combinations at the concentration of drug that produced 80% cell growth inhibition (IC 80 ) were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Assays were conducted in duplicate on two separate occasions with a total incubation time of 48 hours. Experiments were conducted using concentrations of drugs that approximates the EC [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] .The combination of pralatrexate ! gemcitabine was the most cytotoxic combination overall, although methotrexate !…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assays were conducted in duplicate on two separate occasions with a total incubation time of 48 hours. Experiments were conducted using concentrations of drugs that approximates the EC [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] .The combination of pralatrexate ! gemcitabine was the most cytotoxic combination overall, although methotrexate !…”
Section: Resultsmentioning
confidence: 99%
“…Cadman and Eiferman (11) similarly showed the sequence dependency of methotrexate and ara-C in the L1210 model of myeloid leukemia, confirming the preferential accumulation of 1-h-D-arabinofuranosylcytosine 5V-triphosphate in methotrexate-pretreated cells. Using the classic isobologram method of Steel and Peckham, Akutsu et al (12) recently showed that the ordered treatment of methotrexate followed by ara-C is truly synergistic in a mathematical analysis, whereas other schedules of administration (e.g., given together) were potentially antagonistic. The recent emergence of a novel cytidine analogue gemcitabine (2V,2V-difluorodeozycytidine) and its documented activity in very drug-resistant aggressive lymphoma, with an overall response rate of f20%, raises the interesting possibility that combinations of gemcitabine and pralatrexate could be exploited, given their likely greater single-agent activity in lymphoma, in similar synergistic fashion (13,14).…”
mentioning
confidence: 99%
“…8,10,[12][13][14][15][16] Therefore, we studied whether the antagonism between doxorubicin and VCR might be sequence dependent. Indeed, when VCR was given first, 1 day before doxorubicin, VCR induced significant apoptosis.…”
Section: Sequence Dependency Of the Antagonism In Vitro And In Vivomentioning
confidence: 99%
“…[8][9][10][11][12][13] Among others, sequence dependency was proven for the combination of asparaginase and methotrexate for anti-leukemia therapy. 8,10,[12][13][14][15][16] On a molecular level, the effects and signaling pathways induced by many chemotherapeutic drugs have not been analyzed in depth, and the consequences of their combinatorial application remain unclear. 17 As far as we know, no mechanistic data exist so far to explain the sequence dependency of any clinically proven drug combination on a molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…6,15,25,26 We evaluated combinations of clinically relevant drugs belonging to different groups: mitoxantrone (anthracenedione), cisplatin (alkylating-like), dexamethasone (glucocorticosteroid), methotrexate (antifolate), sclareol (labdane diterpene), paclitaxel (taxane) and doxorubicin (anthracycline). In vitro use of these drugs in combination protocols was reported for sclareol and methotrexate, 27,28 in vivo for paclitaxel, cisplatin and dexamethasone; 8,[29][30][31] and with patients for doxorubicin, paclitaxel, mitoxantrone and methotrexate. [16][17][18][32][33][34] Their sequential combination with doxorubicin in a spheroid model was studied in this report.…”
Section: Introductionmentioning
confidence: 99%